(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2022)
Environmental degradation and climate change are having a severe impact on the long-term economic activities around the world. Many countries have recently placed a greater emphasis on green growth to achieve a resilient, low-carbon, and resource-efficient economy that leads to improved quality of life. This gradual shifting towards greener economy model will result in the creation of green jobs and the greening of existing jobs for which workers with green skills will be needed. As a result, it is essential to develop green skills in TVET institutions. In India, green skills have been incorporated into school vocational curricula by Pandit Sunderlal Sharma Central institute of Vocational Education, Bhopal. This study examined the acquisition of green skills by students in senior secondary government schools in Bhopal, Madhya Pradesh where vocational programmes under the National Skills Qualifications Framework were introduced. Data was obtained from a sample of 80 students in class XII who had chosen vocational courses at the secondary level from four selected senior secondary government schools using a self-developed questionnaire. The results revealed that the students were well aware of the green skills, which they had been learning from class IX. However, there were varied responses with low mean and high standard deviation from students about their involvement in practising green skills, despite the fact that the majority of students followed green practises. It is proposed that the existing employability skills syllabus in vocational courses be updated to cover the most recent developments in green technology and green jobs.